Prolonged Survival of Acute Lymphoblastic Leukemia with Intrathecal Treatments for Isolated Central Nervous System Relapse. (31st January 2018) - Gorshein, Elan; Kalathil, Sheila; Gharibo, Mecide
Abstract : Acute lymphoblastic leukemia is commonly cured when diagnosed in the pediatric population. It portends a poorer prognosis if present in adult patients. Although adults frequently achieve complete remission, relapse rates are substantial, particularly among the elderly and high-risk populations. In the absence of prophylactic intrathecal chemotherapy, more than half of patients may develop CNS involvement or relapse, which is associated with significant risk for systemic illness. This report describes a patient with acute lymphoblastic leukemia with repeated isolated CNS relapses. This case should remind clinicians that isolated CNS disease in the absence of systemic recurrence could successfully respond to intrathecal therapy and offer patients a favorable quality of life.